Dosimetric Analysis of IMRT Plans in Head and Neck Cancers to Evaluate the Probability to Decrease Oral Mucositis - Himanshi Khattar; Piyush Kumar; S. Navitha (Perspective of Recent Advances in Medical Research Vol. 12, 2023)
The present study aims to assess the dose going to these unspecified regions termed as pseudo-OARs and if delineation of these structures and prescribing a proper dose constraint will reduce the dose to the oral mucosa without compromising the quality of the treatment plan. A frequent and potentially serious side effect of radiation therapy for head and neck cancer is oral mucositis. When mucositis is severe, it can be painful, make chewing and swallowing difficult, and lead to treatment failures that can result in local recurrence or a drop in overall survival. A total of 10 head and neck cancer patients (six carcinoma buccal mucosa cases and four carcinoma oropharynx) who had been treated by IMRT were selected for the retrospective study. The pseudo-OAR consisted of anterior oral mucosa, part of mandible and maxilla, which was adjacent to the PTV in oropharynx and contralateral buccal mucosa patients. The dose constraint given to the pseudo-OAR was Dmean \(\)30 Gy. Statistical significance was calculated by using a paired t-test. A p- value of <0.05 was considered as statistically significant. The dosimetric parameters of PTV were comparable in both the IMRT arms. The pre-specified objective was fulfilled with both the study arms. The dose homogeneity and conformity was also similar. The dosimetric parameters of other OARs were within the prescribed dose constraints. The Dmean value of the pseudo-OAR in arm I was 31.28 Gy ± 3.55 Gy and 7.87 Gy ± 9.11 Gy in arm II and the p -value was significant (p=0.001), whereas the Dmax in arm I was 61.82 Gy ± 5.91 Gy and 61.23 Gy ± 5.54 Gy in arm II (p=0.6). The dose to the pseudo-OAR in IMRT arm II was reduced drastically by 75%, which was statistically significant. This study emphasises how crucial it is to identify the oral mucosa as a pseudo-OAR in head and neck cancer patients receiving radiation treatment. Clinical studies must optimise dose constraints, which will likely reduce the prevalence and severity of oral mucositis.